Comparison of dose response functions for EBT3 model GafChromic™ film dosimetry system. (May 2018) - Aldelaijan, Saad; Devic, Slobodan
Highlights: Comparison of different radiochromic film response functions. No need to scan film pieces before and after irradiation. Linear dose response for a new, normalized pixel value, response function. Abstract: Objective: Different dose response functions of EBT3 model GafChromic™ film dosimetry system have been compared in terms of sensitivity as well as uncertainty vs. error analysis. We also made an assessment of the necessity of scanning film pieces before and after irradiation. Methods: Pieces of EBT3 film model were irradiated to different dose values in Solid Water (SW) phantom. Based on images scanned in both reflection and transmission mode before and after irradiation, twelve different response functions were calculated. For every response function, a reference radiochromic film dosimetry system was established by generating calibration curve and by performing the error vs. uncertainty analysis. Results: Response functions using pixel values from the green channel demonstrated the highest sensitivity in both transmission and reflection mode. All functions were successfully fitted with rational functional form, and provided an overall one-sigma uncertainty of better than 2% for doses above 2 Gy. Use of pre-scanned images to calculate response functions resulted in negligible improvement in dose measurement accuracy. Conclusion: Although reflection scanning mode provides higher sensitivity and could lead to a more widespread use of radiochromic film dosimetry, it has fairly limited dose range and slightly increased uncertainty when compared to transmission scan based response functions. Double-scanning technique, either in transmission or reflection mode, shows negligible improvement in dose accuracy as well as a negligible increase in dose uncertainty. Normalized pixel value of the images scanned in transmission mode shows linear response in a dose range of up to 11 Gy.